Defining the relationship between phylogeny, clinical manifestation, and phenotype for Trichophyton mentagrophytes/interdigitale complex; a literature review and taxonomic recommendations - Švarcová, Michaela; Větrovský, Tomáš; Kolařík, Miroslav; Hubka, Vit (Medical mycology, 2023)
This study looked for correlations between molecular identification, clinical manifestation, and morphology for Trichophyton interdigitale and Trichophyton mentagrophytes. For this purpose, a total of 110 isolates were obtained from Czech patients with various clinical manifestations of dermatophytosis. Phenotypic characters were analyzed, and the strains were characterized using multilocus sequence typing. Among the 12 measured/scored phenotypic features, statistically significant differences were found only in growth rates at 37 °C and in the production of spiral hyphae, but none of these features is diagnostic. Correlations were found between T. interdigitale and higher age of patients and between clinical manifestations such as tinea pedis or onychomychosis. The MLST approach showed that internal transcribed spacer (ITS) genotyping of T. mentagrophytes isolates has limited practical benefits because of extensive gene flow between sublineages. Based on our results and previous studies, there are few taxonomic arguments for preserving both species names. The species show a lack of monophyly and unique morphology. On the other hand, some genotypes are associated with predominant clinical manifestations and sources of infections, which keep those names alive. This practice is questionable because the use of both names confuses identification, leading to difficulty in comparing epidemiological studies. The current identification method using ITS genotyping is ambiguous for some isolates and is not user-friendly. Additionally, identification tools such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry fail to distinguish these species. To avoid further confusion and to simplify identification in practice, we recommend using the name T. mentagrophytes for the entire complex. When clear differentiation of populations corresponding to T. interdigitale and Trichophyton indotineae is possible based on molecular data, we recommend optionally using a variety rank: T. mentagrophytes var. interdigitale and T. mentagrophytes var. indotineae.
Keywords: fylogeneze; DNA, Ribosomal Spacer; mezerníky ribozomální DNA; Trichophyton; DNA, Fungal; multilokusová sekvenční typizace; Sequence Analysis, DNA; Phenotype; Tinea; zvířata; Animals; Multilocus Sequence Typing; tinea; DNA fungální; Phylogeny; fenotyp; sekvenční analýza DNA